EVIDENCE-CLASSIFIED DIAGNOSIS OF INTERCONNECTED IGNITION-COIL, CONNECTOR, AND CONTROL-UNIT DRIVER FAULTS - Joyfull Sidney Payumi; Nodi Poluan Sompie; Franklin Bawano (CV. TOTUS TUUS, 2026)
Coil-on-plug (COP) ignition faults can involve the coil, connector, harness, and electronic control unit (ECU), yet a single workshop case cannot establish the initiating component or transient chronology. This evidence-classified diagnostic case examined one Daihatsu Xenia 1.0 Non-VVT-i with an EJ-DE three-cylinder gasoline engine presenting vibration, misfire, reported loss of power, and reported increased fuel consumption. The available field record documented visual inspection, multimeter observations of supply and ignition trigger/feedback (IGT/IGF) lines, coil substitution, guarded substitution with a known-good ECU, on-board diagnostics II (OBD-II) scanning, internal ECU and connector inspection, corrective repair, and preliminary workshop verification. The multimeter did not detect comparable IGT/IGF indications on cylinders 2 and 3; replacing the suspected coils did not resolve the symptoms; and the donor ECU displayed diagnostic trouble codes (DTCs) P0300, P0352, P0353, and P0171. Degraded female connector contacts and visible damage along the original ECU ignition-driver path were subsequently observed. Repair of the documented defects was followed by restored continuity and stable operation during an unspecified workshop observation period. The evidence supports system-level diagnosis of an interconnected coil-connector-ECU fault, but not a proven cascade from coil switching to ECU damage. The principal contribution is a transparent reporting framework that separates direct observation, diagnostically supported interpretation, and unmeasured mechanism. The case also provides a safety-conscious diagnostic sequence for workshop and proposed vocational-learning use.